2014
DOI: 10.1017/s0967199414000197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal ageing on ICSI outcomes and embryo development in relation to oocytes morphological characteristics of birefringent structures

Abstract: SummaryThe aim of this study was to determine the morphological characteristics of the older reproductive aged women's oocytes and to reveal the influence of these characteristics on intra-cytoplasmic sperm injection (ICSI) outcomes. The oocytes of women older than 35 years of age were evaluated retrospectively. Non-invasive polarization microscopy (PolScope) examinations of mature oocytes were performed by measurement of meiotic spindles' length, area and retardance and zona pellucida thickness and retardance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The oocytes having meiotic spindle lengths of more than 12 µm possessed higher chances of producing blastocysts when compared to the oocytes with meiotic spindle lengths of 10-12 µm or less than 10 µm (Rama Raju et al, 2007). Similarly, Korkmaz, Tekin, Sakinci, and Ercan (2015) found a correlation between the length of spindles and fertilization success of women older than 35 years old (Korkmaz et al, 2015). In a recent study by Tomari et al (2018) reported that the oocytes whose meiotic spindle sizes were between 90 and 120 μm 2 had higher fertilization, blastocyst formation, and clinical pregnancy rates when compared with the oocytes having larger or smaller spindle sizes.…”
Section: Extracytoplasmic Factor Property Outcomementioning
confidence: 95%
See 1 more Smart Citation
“…The oocytes having meiotic spindle lengths of more than 12 µm possessed higher chances of producing blastocysts when compared to the oocytes with meiotic spindle lengths of 10-12 µm or less than 10 µm (Rama Raju et al, 2007). Similarly, Korkmaz, Tekin, Sakinci, and Ercan (2015) found a correlation between the length of spindles and fertilization success of women older than 35 years old (Korkmaz et al, 2015). In a recent study by Tomari et al (2018) reported that the oocytes whose meiotic spindle sizes were between 90 and 120 μm 2 had higher fertilization, blastocyst formation, and clinical pregnancy rates when compared with the oocytes having larger or smaller spindle sizes.…”
Section: Extracytoplasmic Factor Property Outcomementioning
confidence: 95%
“…• Visualization ↑ ZP birefringence (Madaschi et al, 2009) ↑ fertilization rate (Braga et al, 2008;Garcia-Oro et al, 2017;Gonzalez-Ortega et al, 2016;Petersen et al, 2009;Rama Raju et al, 2007) ↑ normal pronuclei appearance (Petersen et al, 2009) ↑ cleavage rate (Petersen et al, 2009) ↑ Day 3 embryo quality (Petersen et al, 2009) ↑ embryo quality (Gonzalez-Ortega et al, 2016) ↑ blastocyst development (Braga et al, 2008;Garcia-Oro et al, 2017;Petersen et al, 2009;Rama Raju et al, 2007) ↑ implantation rate (Garcia-Oro et al, 2017;Madaschi et al, 2008) ↑ conception cycle (Gonzalez-Ortega et al, 2016) ↑ pregnancy rate (Konc et al, 2004;Madaschi et al, 2008) • Longer spindle length ↑ Fertilization success (Korkmaz et al, 2015) ↑ blastocyst formation (Rama Raju et al, 2007) • Misaligned meiotic spindle position ↑ Fertilization defect (Rienzi et al, 2003) • Localization to beneath or adjacent to PB ↑ Fertilization rate (Fang et al, 2007) • Higher retardance ↑ Better pronuclear score (Shen et al, 2006) ↑ blastocyst formation (Rama Raju et al, 2007) ↑ pregnancy rate (Shen et al, 2006) • Higher density ↑ Pregnancy rate (Kilani et al, 2009) • Normally appearing spindles ↑ Fertilization rate (Kilani et al, 2009;Tilia et al, 2020) ↑ Day 3 embryo development (Tilia et al, 2020) ↑ blastocyst quality (Tilia et al, 2020) ↑ euploid blastocyst number (Tilia et al, 2020) ↑ implantation rate (Kilani et al, 2009) ↑ pregnancy rate (Kilani et al, 2009) ↑ live birth rate (Kilani et al, 2009) • Fine aligned ↑ Embryo cleavage (Asa et al, 2017) ↑ embryo quality <...>…”
Section: Meiotic Spindle Outcomementioning
confidence: 99%
“…Interestingly enough, we also reported that an increased MS size was associated with early embryo development arrest, before reaching the blastocyst stage [ 3 ]. Furthermore, the impact of female age on oocyte birefringent structures has been previously described and, in general, considered to be quite limited [ 3 , 51 , 54 , 55 ]. In the present study, comparable maturation, fertilization, and cleavage rates were observed in the two groups, suggesting that in the analysed population the woman’s age may have exerted only a limited effect (if any) on oocyte quality and that the significant differences observed in the birefringent structures were likely to be related mainly to factors other than age.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies assessed the effect of MS presence in human MII oocytes on ART outcomes, however, with controversial results. More studies showed that the presence of a spindle is a predictive factor of fertilization (Konc et al, 2004;Shen et al, 2005;Raju et al, 2007;Madaschi et al, 2008;Kilani et al, 2011;Kilani & Chapman, 2014;Korkmaz et al, 2015;Matsunaga & Horiuchi, 2015;González-Ortega et al, 2016;Raubenheimer, 2016), whereas others found insignificant differences in fertilization rates between the oocytes with and without a detectable MS (Moon et al, 2003;Fang et al, 2007;Ebner et al, 2009). A meta-analysis study investigated the finding of 10 trials about the influence of MS visualization in human oocytes on ICSI outcomes (Petersen et al, 2009).…”
Section: Spindle Presence/position and Art Outcomesmentioning
confidence: 99%